Exploring the sheen: a review of research advances on fruit glossiness - Dong, Shuchao; Li, Jiaxin; Zhang, Jingwen; Song, Liuxia; Wang, Yinlei; Zhao, Liping; Chen, Jie; Brotman, Yariv; Zhao, Tongmin (Frontiers in Plant Science, 2025)
Fruit glossiness is a visually appealing trait that positively influences consumer preferences and market value. Despite its commercial importance, the biological basis of fruit glossiness has only recently gained attention. This review provides a comprehensive overview of the current understanding of fruit glossiness, with emphasis on its physiological, biochemical, and molecular underpinnings. Fruit glossiness is primarily determined by the structure and composition of the fruit cuticle, which consists of cutin and waxes. The accumulation, transport, and organization of these components dictate surface reflectivity and gloss levels. Various instrumental approaches, including gloss meters, luster sensors, spectrophotometers, and imaging systems, have been developed to objectively quantify glossiness, complementing traditional visual assessments. Advances in molecular genetics have revealed that genes involved in cuticle biosynthesis and regulation, such as WAX2, CER1, GPAT6, and SHINE family transcription factors, play critical roles in determining surface gloss. In cucumber and tomato, genetic dissection has uncovered distinct regulatory pathways involving wax and cutin metabolism, vesicle trafficking, and transcriptional control. Emerging evidence from other fruit species such as citrus, bilberry, and grape further supports a conserved yet diverse genetic architecture underlying fruit glossiness. Collectively, this review highlights the complex interplay between structural biology, environmental cues, and gene regulation in shaping fruit surface properties, and identifies promising directions for future research and crop improvement strategies.